2012
DOI: 10.1111/j.1540-5850.2012.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Form of Government and Property Tax Limits on Local Finance in the Context of Revenue and Expenditure Simultaneity

Abstract: This paper examines the impact of the form of government and state-imposed property tax limits on municipal finance. We suggest that municipal revenues and expenditures are determined concurrently and estimate revenue and expenditure functions as simultaneous equations. We use the instrumental variable approach and fixed effects to address revenue and expenditure endogeneity. By testing the model on a cross-section of rich municipal data for fiscal year 2002, we find evidence that revenues and expenditures are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
0
41
1
Order By: Relevance
“…Some studies have shown that TELs effectively restrict municipal revenues and spending (Chapman & Gorina, ; Jordan & Wagner, ; Preston & Ichniowski, ; Shadbegian, , ); others have demonstrated that the effects of TELs are asymmetric across communities and particularly constraining to the growth of poorer localities (Bae & Gais, ; Mullins, ); still others have not found any consistent effects (for a review, see Mullins & Wallin, ). No research has yet assessed the effects of TELs on annexation outcomes.…”
Section: Effects Of Annexation On Local Financementioning
confidence: 99%
“…Some studies have shown that TELs effectively restrict municipal revenues and spending (Chapman & Gorina, ; Jordan & Wagner, ; Preston & Ichniowski, ; Shadbegian, , ); others have demonstrated that the effects of TELs are asymmetric across communities and particularly constraining to the growth of poorer localities (Bae & Gais, ; Mullins, ); still others have not found any consistent effects (for a review, see Mullins & Wallin, ). No research has yet assessed the effects of TELs on annexation outcomes.…”
Section: Effects Of Annexation On Local Financementioning
confidence: 99%
“…On a higher level, cities may also be limited in their actions by their state governments (Benton, 2003;Chapman & Gorina, 2012). This doesn't mean that local structures don't matter -only that there are other structures that matter as well.…”
Section: A Renewed Institutionalismmentioning
confidence: 99%
“…This variable is typically used to measure efficiency (Booms, 1966;Chapman & Gorina, 2012;Deno & Mehay, 1987;French, 2004;Hayes & Chang, 1990;Jung, 2006;Lineberry & Fowler, 1967;Morgan & Pelissero, 1980;Stumm & Corrigan, 1998). As stated in Chapter 1 this is more a measure of spending than of actual efficiency.…”
Section: Research Design and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations